2018
DOI: 10.1371/journal.pone.0202019
|View full text |Cite
|
Sign up to set email alerts
|

Compression in cultural evolution: Homogeneity and structure in the emergence and evolution of a large-scale online collaborative art project

Abstract: Cultural evolutionary theory provides a framework for explaining change in population-level distributions. A consistent finding in the literature is that multiple transmission episodes shape a distribution of cultural traits to become more compressible, i.e., a set of derived traits are more compressed than their ancestral forms. Importantly, this amplification of compressible patterns can become manifest in two ways, either via the homogenisation of variation or through the organisation of variation into stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Our work add to a list of notable Internet performances, including Reddit Place and Twitch Plays Pokémon, which highlighted how intelligent goal-oriented behavior, typical of higher cognitive functions, can emerge in a decentralized manner from distributed social systems [1,11]. At the same time, our work employs a real-time democratic consensus system based on language, instead of simpler local aggregation rules typically used in other Internet performances.…”
Section: Discussionmentioning
confidence: 99%
“…Our work add to a list of notable Internet performances, including Reddit Place and Twitch Plays Pokémon, which highlighted how intelligent goal-oriented behavior, typical of higher cognitive functions, can emerge in a decentralized manner from distributed social systems [1,11]. At the same time, our work employs a real-time democratic consensus system based on language, instead of simpler local aggregation rules typically used in other Internet performances.…”
Section: Discussionmentioning
confidence: 99%
“…Youngblood (2019) tracked the spread of music samples among hip-hop and electronic producers and showed that, thanks to digital sampling technologies, their networks of collaborations are no longer constrained by geographical proximity. Müller & Winters (2018) analysed the evolution of Reddit Place, a social media experiment in which any registered user could place a single coloured pixel on a 1,000 x 1,000 pixels online digital canvas every 5 to 20 minutes for three days. The project involved 1 million individuals that placed more than million pixels.…”
Section: Digital Cumulative Culturementioning
confidence: 99%
“…On the other hand, despite its undisputed special status, language is no longer seen as the "odd one out" among our cognitive and cultural traits. Instead, an integrative view sees language as bearing important commonalities with other phenomena, which is why phenomena as different as the construction of paper airplanes (Caldwell & Millen 2008), the evolution of a collaborative art project (Müller & Winters 2018), diachronic changes in ancient coin designs (Pavlek, Winters & Morin 2019), and the evolution of language(s) can be investigated in a shared theoretical framework. The 2016 founding of the Cultural Evolution Society bears witness to the appeal of such an integrative approach to language, cognition, and culture.…”
Section: An Integrative Approach To Language Dynamicsmentioning
confidence: 99%